Effects of in vivo application of an overnight patch containing Allium cepa, allantoin, and pentaglycan on hypertrophic scars and keloids: Clinical, videocapillaroscopic, and ultrasonographic study. Issue 1 (28th December 2020) - Campanati, Anna; Ceccarelli, Gabriele; Brisigotti, Valerio; Molinelli, Elisa; Martina, Emanuela; Talevi, Davide; Marconi, Barbara; Giannoni, Melania; Markantoni, Vasiliki; Gregoriou, Stamatios; Kontochristopoulos, George; Offidani, Annamaria
Abstract: Several therapeutic approaches have been described for their treatment of hypertrophic scars and keloids, but to date, the optimal treatment has not been established yet. Our in vivo study was conducted to evaluate the effect of a medical device consisting in an adhesive patch containing onion extract ( Allium cepa ) 10%, allantoin 1%, and pentaglycan 4% (Kaloidon patch) on hypertrophic scars and keloids. Thirty‐nine patients with hypertrophic scars and seven patients with keloids were asked to apply an adhesive patch containing Allium cepa, allantoin, and pentaglycan once/day for at least 8 h consecutively, for 24 weeks. Patients were reevaluated 6 weeks (T6), 12 weeks (T12), and 24 weeks (T24) after starting the treatment through POSAS scale v 2.0, ultrasonographic, and videocapillaroscopic assessment. The investigated medical device was able to induce a significant improvement of POSAS starting from T12, with a positive amelioration trend until T24. However the patient‐assessed POSAS sub‐items showed improvement already after 6 weeks, whereas a significant improvement of the observer‐assessed POSAS sub‐items was observed only after 12 weeks ( P  < .001). Ultrasonography and intravital videocapillaroscopy confirmed a significant improvement of skin scars thickness ( P  < .001) and vascularization ( P  < .001) after 12 weeks of medical device application at least, with increasing improvement until T24. Applying an adhesive patch containing Allium cepa, allantoin, and pentaglycan once a day for at least 8 consecutive hours seems to be able to improve the clinical and morphological characteristics of the scars of the skin in 24 weeks.